Высокочувствительный модуляционный радиометрический приемник диапазона частот 92...96 ГГц - Berezhnoy, V. A.; Kuzhel, V. I.; Ignatenko, V. S.; Kondrashenko, M. A.; Ryabchuk, A. F.; Cherniy, B. S. (PE "Politekhperiodika", Book and Journal Publishers, 2003)
The receiver was developed in two versions based on a superheterodyne scheme with synchronous detection. It includes a noise‑adding generator that provides additional noise in the receiving channel of 4–340 K. Operating in the 92...96 GHz frequency range, the receiver ensures fluctuation sensitivity (with an integration time constant of 1 s) of 0.01 and 0.03 K/√Hz, as well as linearity of the output voltage within the input noise signal range of 100–800 K.